2022
DOI: 10.3390/coatings12081070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrothermal Sealing on the High Cycle Fatigue Behavior of the Anodized 6082 Aluminum Alloy

Abstract: For aluminum alloys, anodizing is a common electrochemical surface treatment to allow for protection against corrosion and wear. The produced conversion layers are first sealed in industrial processes to further enhance the corrosion protection by closing the coating surface pores. In their lifetime, anodized components often undergo cyclic loadings. However, despite the relevance of a sealing treatment, there is a lack of systematic studies regarding its influence on the fatigue behavior of anodized aluminum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…Further, the tested oxide coatings in their study were hydrothermally sealed, which can also have a major influence on the fatigue resistance. [26] The observed failure behavior of the anodized specimens was also shown by Vie et al [46] They combined acoustic emission and microstructural analysis confirmed that only after few cyclic loadings numerous cracks are already initiated in the brittle anodic coating and that after 15% of the fatigue life the crack number reaches a saturation value. Due to further cyclic loading, although there are multicrack initiation sites in the coating, only one main crack propagates toward the substrate leading to fatigue failure and fracture.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Further, the tested oxide coatings in their study were hydrothermally sealed, which can also have a major influence on the fatigue resistance. [26] The observed failure behavior of the anodized specimens was also shown by Vie et al [46] They combined acoustic emission and microstructural analysis confirmed that only after few cyclic loadings numerous cracks are already initiated in the brittle anodic coating and that after 15% of the fatigue life the crack number reaches a saturation value. Due to further cyclic loading, although there are multicrack initiation sites in the coating, only one main crack propagates toward the substrate leading to fatigue failure and fracture.…”
Section: Discussionsupporting
confidence: 70%
“…The experimental determined fatigue data points were curve‐fit using a logarithmic model provided by Rateick et al [ 9 ] This empirical model allows for a high compliance of the experimentally determined data points with the calculated progression of the fatigue life as it was developed by Rateick et al [ 9 ] for a hardanodized aluminum alloy and was successfully used in previous own studies representing the fatigue curve of coated specimens. [ 22,26,28 ] logNf=A+Blog(σmaxC)$$log N_{\text{f}} = A + B \cdot log \left(\right. \left(\sigma\right)_{\text{max}} - C \left.\right)$$…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations